Experimental studies on in-plane connections of composite beam-precast concrete shear wall under reversed cyclic loading. (December 2021) - Xia, Kang; Hu, Xiang; Xue, Weichen
Abstract: Precast concrete frame-shear wall structure is a typical structural system in high-rise buildings, in which in-plane beam-shear wall connections play an important role during the earthquake. An in-plane composite beam-precast concrete shear wall connection, composed of composite beam, precast shear wall and cast-in-place (CIP) joint region, is introduced. Two precast specimens and two control CIP specimens were loaded under reversed cyclic loading with axial compression ratios ( R ) of both 0.12 and 0.30. The study showed the failure pattern of precast specimens, which was flexural failure occurring at the beam end, was consistent with that of the CIP specimens. No obvious damages took place in the joint region and shear wall. The hysteresis curves of four specimens are relatively plumper presenting a pinching behavior, and the ability of precast specimens to dissipate energy is coincident with that of the CIP specimens. Precast specimens could achieve the comparable loading capacity to the control CIP specimens, and the differences between them are approximately 3% ( R = 0.12) and 6% ( R = 0.30), respectively. The ductility of precast specimens is 4.23 ( R = 0.12), 3.47 ( R = 0.30), within 7% variation from that of the CIP specimens. Precast specimens exhibit similar stiffness degradation to the CIP specimens. Moreover, a hysteretic four-linear restoring force model is proposed.